Napływ bezpośrednich inwestycji zagranicznych jako czynnik dynamizacji procesów rozwoju miasta Wrocław - Bobowski, Sebastian (Inflow of Foreign Direct Investments as a Factors of Dynamization of Development's Processes of Wroclaw Agglomeration, 2007)
The principled aim of this article is to point at the dynamics of foreign direct investments in Wroclaw through the years of transformation. The effectiveness of local administration, reasonable budgetary policy, large-scale infrastructure projects, co-financed by European structural funds, are the main factors that influence competitiveness of region and its attractiveness for investors.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Ekonomia i Międzynarodowe Stosunki Gospodarcze (14); 2007; nr 1164, s. 55-65